THE MARKET REACTION ON NORDIC COUNTRIES’ STOCK - Tolppanen, Roosa (My University, 2018)
The analyst recommendations are crucial help for the traders, as they have to deal with a vast amount of information regarding the stock markets. There are few studies that have found abnormal returns to occur after publication of recommendations. The theories of the CAPM and the EMH can not explain this event. This study researches if recommendations bring value to traders. The main question of this study is whether it is possible to earn abnormal returns following recommendations. This is examined in two different ways. First, the four portfolios are generated following the analysts’ recommendations. These portfolios are: ”Buy”, ”Hold”, ”Sell” and ”Strong sell”. Further, I compare the returns with the benchmark market portfolio, which is chosen to be OMX Nordic 40 index. The market model is applied to get the results. The second part takes into account the stock characteristics and the recommendation. This study finds that it is not possible to earn abnormal returns in the Nordic’s stock market by following analysts’ recommendations. Further, the stock characteristics were researched by finding out if the stocks that were owing the same recommendation had something in common with its charasteristics. In this study Price-to-Book, return on investment, size and share turnover are found to have a significant effect.
Keywords: Recommendation; Analyst; Abnormal return; Stock characteristic; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|